Enfoque integrativo multidimensional e intervenciones mente-cuerpo en el manejo del dolor crónico: el caso de una adulta mayor - Cornejo D., Juan Pablo; Barros L., Paulina Angélica (Revista Hospital Clínico Universidad de Chile, 2015)
Chronic pain is common in older adults, it is difficult to handle and has important medical and psychiatric comorbidity. A case of Elderly with chronic pain who received integrative multidimensional psychotherapy. Favorable changes seen in reduction of pain and life quality. It argues that the multidimensional integrative psychotherapy can be effective in the management of chronic pain in older adults.